Penerapan Model Pembelajaran Picture and Picture dalam Meningkatkan Hasil Psikomotorik pada Siswa di Kelas II MIS Nurur Rahman Kota Jambi - Haikal Pikri (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study is based on the importance of learning obligatory prayers in prayer movements at MIS Nurur Rahman, Jambi City, because most students at MIS Nurur Rahman, Jambi City, especially in class II, have difficulty in performing obligatory prayers correctly and sequentially. Therefore, the purpose of this study is to determine the planning, implementation, and evaluation of obligatory prayer learning by applying the picture and picture learning model in the era of the Independent Curriculum learning in class II of MIS Nurur Rahman, Jambi City. To achieve these goals, the researcher used Classroom Action Research (CAR) with the method used, namely Classroom Actions Research. Data collection techniques used in this study were observation, documentation, pretest (initial test) and posttest (final test). The selected data sources used teacher activity data and student activity data. The results of this study are 1) planning Islamic religious learning in prayer movements by applying the picture and picture learning model, determining learning objectives, Islamic religious learning designs in prayer movements with the picture and picture learning model, learning activities, learning assessments; 2) implementation of Islamic religious learning in prayer movements with the picture and picture learning model in the Merdeka Belajar Curriculum era in class II MIS Nurur Rahman which includes planning, acting, observing, and reflecting; 3) Islamic religious learning in prayer movements in the Merdeka Belajar Curriculum era in class II MIS Nurur Rahman Jambi City includes an understanding of the picture and picture learning model in this classroom action research (PTK).